Development Learning Design Based on Metacognitive Strategies Oriented to Critical Thinking Skill - Madya Hutabarat; Caswita Caswita; Suharsono Suharsono (IIES Independent, 2019)
The purpose of this study is to develop a mathematical learning design based on metacognitive strategies that are oriented to critical thinking skills that are valid, practical and effective in solid geometry. The research was carried out with stages in Nieveen's model that begins with preliminary research, prototyping stage, and assessment stage. The field test design uses the pretest-posttest control group design. Data collection used a validation sheet, student and teacher questionnaire responses, and test instruments of critical thinking skills. Respectively to determine the validity of learning design, the level of practicality, and the effectivity of learning design. Validity and practicality were analyzed by using deskiptif statistics, while effectivity were analyzed by Mann Whitney U. Classical completeness, critical thinking skills, and improving critical thinking skills of students who apply learning based on metacognitive strategies are better than conventional learning. Therefore the design of learning based on metacognitive strategies is feasible because it meets the criteria of valid, practical and effective to improve students' critical thinking skills.